A fuzzy multi-criteria decision support system for evaluating subsea oil pipeline routing criteria in East Malaysia - Balogun, A.-L. (Springer Verlag, 2015)
Selecting suitable pipeline routes is essential to the success of any oil exploration and transportation project, and proper prioritization of the diverse routing criteria is an integral component of the route selection endeavor. However, recent researches reveal that accurate prioritization of routing criteria, particularly in an offshore/subsea environment, has not been sufficiently addressed. With global attention rapidly expanding from terrestrial exploration to offshore and subsea oil pipeline operations, this study addresses the offshore pipeline routing ranking concerns. A hybrid multi-criteria decision support system was developed by integrating fuzzy logic-based approximate reasoning (AR) and Analytic Hierarchy Process (AHP) mathematical models. Twelve diverse criteria and sub-criteria in an oil-rich basin offshore east Malaysia were examined to determine their impact in the selection of an optimal pipeline route in the area. These were subsequently classified into three broad categories: economic, engineering, and environmental routing criteria. The integrated system (AR-AHP) was used to determine the relative importance of the criteria using different fuzzy membership functions and linguistic variables. Final results showed that the environmental criteria in the study area have the highest aggregated priority and influence (61.4Â ) followed by the engineering criteria (27.6Â ) and the economic criteria (11Â ) datasets, respectively. This study thus establishes the fact that preservation of environmental factors is superior to the other strategic criteria in the marine study area. Â© 2015, Springer-Verlag Berlin Heidelberg.